2006
DOI: 10.1002/aps.108
|View full text |Cite
|
Sign up to set email alerts
|

The idea of mutual affect

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…At the same time that she was calming herself, the supervisor was already arriving at new insights and creating an emotionally safe space into which she invited the supervisee, who, in turn, was regulating herself at the same time. In line with Erzar and Kompan Erzar (2006), this process can be referred to as affective autoregulation, which in this case applies to the processes of self-regulation and mutual regulation. Tronick (1998) has suggested that in the process of mutual regulation each partner affects the other's "state of consciousness."…”
Section: Theme 3: Reestablishing a Connectionmentioning
confidence: 87%
“…At the same time that she was calming herself, the supervisor was already arriving at new insights and creating an emotionally safe space into which she invited the supervisee, who, in turn, was regulating herself at the same time. In line with Erzar and Kompan Erzar (2006), this process can be referred to as affective autoregulation, which in this case applies to the processes of self-regulation and mutual regulation. Tronick (1998) has suggested that in the process of mutual regulation each partner affects the other's "state of consciousness."…”
Section: Theme 3: Reestablishing a Connectionmentioning
confidence: 87%
“…Although conceptualizations of core relationship themes relating to mutual interaction between partners are not new in the field of couple therapy (e.g., “mutual affective regulation,” see Erzar & Erzar, ; “power inequality within couple,” see Ward & Knudson‐Martin, ), one area of research on couple dynamics gaining increased attention over the past 15 years is dyadic coping (DC). DC has been defined as “the interplay between the stress signals of one partner and the coping reactions of the other, a genuine act of shared coping” (Revenson, Kayser, & Bodenmann, , p. 4).…”
Section: Dyadic Coping In Couple Therapy Process: An Exploratory Studymentioning
confidence: 99%
“…Los hijos aprenden imitando valores, preocupaciones y conductas 20 y podría suponerse que también ocurre lo mismo con la administración de la imagen y el peso, pudiendo constituir un factor de riesgo para desarrollar trastornos del comer 21 .…”
Section: N V E S T I G a C I ó Nunclassified